Factor analysis of quality assurance practices in small and medium-sized road-construction projects: A South African perspective - Nyakala, Kgashane Stephen; Pretorius, Jan-Harm; Vermeulen, Andre (Acta Structilia, 2019)
Although implementing quality assurance (QA) processes in construction is important in the South African economy, small and medium-sized enterprises (SMEs) faced difficulties in improving rural road infrastructure and high quality roads. Hardly any effort is made on to how sustain quality in road-project construction through suitable construction strategy in local governments. This article aims to analyse and examine the quality of road-construction projects built by SMEs contractors in Mopani District Municipality, South Africa. The article follows a quantitative survey approach in which a three-section questionnaire was administered to 160 purposively selected road-building practitioners in South African construction SMEs. The questionnaire was structured into three parts, which sought the participants’ profile, identified the quality assurance practices (QAPs) incorporated in the construction SMEs’ road-building programmes, and identified the factors that negatively influence the implementation of QA processes. Data was analysed using the Statistical Package for the Social Sciences (SPSS) version 23. Descriptive statistics was used to determine the reliability of the various constructs, mean scores, and standard deviations. The empirical findings established eight QAPs that were reliable and valid for implementation processes that can control or minimise their causes of poor quality in projects undertaken by construction SMEs’ level of skill acquisition. These are: project planning and control techniques; project construction design; process implementation and process improvement; financial management; organisational structures; involvement of people, as well as quality standards and measurements. The eight factors attained high Cronbach Alpha values above the recommended 0.70, which indicates high internal consistencies among the sub-scales. This article is significant in that project managers working in similar environments may use the results of this study either as diagnostic tools or as a reference benchmark for strategic interventions in solving construction projects-related problems. The researchers also recommend that these practices are for QA in construction projects undertaken by SMEs in South Africa.